Eksistensi Keberagaman Jajanan Pagi Masyarakat Palembang - Oktaviani, Ria Resti; Syarifuddin, Syarifuddin (Universitas Muhammadiyah Palembang, 2024)
The topic raised in this article is about the existence of the diversity of morning snacks for the people of Palembang in 2014-2021, is a study of various kinds of food sold in the morning in the city of Palembang. The existence of morning snacks in the community still exists even though morning snacks are only as a support before lunch. In this study the method used is a qualitative method by collecting primary and secondary sources through literature study, observation, and direct interviews. There is also a sociological approach that looks at the development of society in Palembang. The purpose of this research is to encourage local wisdom, especially food, to redevelop existing culinary cultural values and to preserve morning food in the future so that it still exists. Thus, it is hoped that the local wisdom of Palembang city food will be able to exist and still be known, enjoyed, and liked by the people of Palembang and the general public.